Not all that glitters is metal: a rare case of mechanical small bowel obstruction - Kulkarni, Shrirang V.; Saxena, Sagar; Sarita, S. (International Surgery Journal, 2025)
Mechanical small bowel obstruction (MSBO) is a common surgical emergency presenting usually because of adhesions due previous abdominal surgeries. Fecolith are usually present in large bowel and are formed mainly due to stasis and dehydration. Small bowel fecolith are extremely rare cause of MSBO which are usually present in setting of inflammatory bowel disease and divertculae. We present a case of acute MSBO due to small bowel fecolith in a frail elderly lady with Dengue fever, who was suspected to have ingested metallic foreign bodies. An emergency mini laparotomy was performed with extraction of fecolith from the distal ileum with resection of strictured distal ileum and end to end ileo-ileal anastomosis. The patient developed features of peritonitis on post-operative day 4 and revealed massive hemoperitoneum with anastomotic leak and was managed with peritoneal lavage and double barrel stoma formation. She was resuscitated with blood products but continued to deteriorate during her post-operative course. This case report aims to analyse and present options which could have been done as a part of damage control surgery, rather than going ahead with a definitive procedure.